Thai EFL Students’ Perceptions of Development of English Reading Comprehension on Buddhist Contents Through PSQ6R Technique - Chatkeaw, Phramahakeerati; Tachom, Khomkrit (Journal of International Buddhist Studies, 2020)
This research aimed to study the Thai EFL students’ perception of the development of English reading comprehension on Bud- dhist contents through PSQ6R technique. The sample included 47 students enrolled in Dhamma in English course at Nakhon Lampang Buddhist College in the 1st semester of academic year 2020. The samples were selected by the purposive selection method. The instrument for collecting data was a question- naire. The data analysis was done using descriptive statistics which are percentage, mean score, and standard deviation. The research result revealed that the students strongly satisfied (x =4.59) with the development of English reading comprehension on Buddhist contents through PSQ6R techniques.